Implementasi Pelaksanaan Pasal 3 dan Pasal 8 Peraturan Pemerintah Nomor 10 Tahun 1983 Jo Peraturan Pemerintah Nomor 45 Tahun 1990 Bagi PNS yang Bercerai di Kabupaten Tebo - Sari, Indah; Suzanalisa, Suzanalisa; Zachman, Nuraini (Legalitas: Jurnal Hukum, 2024)
The solution to major problems between husband and wife in disharmonious households is to divorce, including the household of a Civil Servant. This also happens in the Tebo Regency Civil Servant environment. The implementation of Civil Servant Percerana in Tebo Regency refers to Government Regulation Number 10 of 1983 in conjunction with Government Regulation Number 45 of 1990, so this paper aims to conduct a study of the Implementation of Article 3 and Article 8 of Government Regulation Number 10 of 1983 in conjunction with Government Regulation Number 45 1990 for civil servants who divorced in Tebo Regency.